ATTITUDES AND EXPERIENCES OF CLASSROOM SCIENCE: CHILDREN’S VOICES - Ward, Gillian; Donnan, Lauren E; McNabb, Kirsten (UPI Press, 2016)
This article draws on two studies that examined primary children’s attitudes towards science in the classroom and their experiences of science. Through the data drawn from semi-structured interviews, it was evident that the children were mostly positive about science, but their experiences of science in the classroom were not always how they would prefer their science learning to proceed. The findings highlight aspects of their experiences that enhanced or detracted from their interest in science. In particular, the students stated the importance of being taught relevant and meaningful science in a collaborative context. Children’s out-of-school contexts also became important in their learning of science. These findings are discussed, and suggestions are made for ways in which teachers can make changes to their planning and teaching in order to support positive attitudes to science within the classroom.